Susceptibility of Four Species of Aphids in Wheat to Seven Insecticides and Its Relationship to Detoxifying Enzymes - Gong, Peipan; Chen, Defeng; Wang, Chao; Li, Mengyi; Li, Xinan; Zhang, Yunhui; Li, Xiangrui; Zhu, Xun (Frontiers in Physiology, 2021)
Sitobion avenae (Fabricius), Rhopalosiphum padi (Linnaeus), Schizaphis graminum (Rondani), and Metopolophium dirhodum (Walker) (Hemiptera: Aphididae) are important pests of wheat and other cereals worldwide. In this study, the susceptibilities of four wheat aphid species to seven insecticides were assessed. Furthermore, the activities of carboxylesterase (CarE), glutathione S-transferase (GSTs), and cytochrome P450 monooxygenase (P450s) were determined in imidacloprid treated and untreated aphids. The results showed that the susceptibilities of four wheat aphid species to tested insecticides are different and M. dirhodum has shown higher tolerance to most insecticides. Relatively higher CarE and GST activities were observed in M. dirhodum, and P450s activities increased significantly in response to imidacloprid treatment. Moreover, susceptibility to imidacloprid were increased by the oxidase inhibitor piperonyl butoxide in M. dirhodum (20-fold). The results we have obtained imply that P450s play important role in imidacloprid metabolic process in M. dirhodum. We suggest that a highly species-specific approach is essential for managing M. dirhodum.